Evaluated strategies to increase attraction and retention of health workers in remote and rural areas - Carmen Dolea; Laura Stormont; Jean-Marc Braichet (The World Health Organization, 2010)
The lack of health workers in remote and rural areas is a worldwide concern. Many countries have proposed and implemented interventions to address this issue, but very little is known about the effectiveness of such interventions and their sustainability in the long run. This paper provides an analysis of the effectiveness of interventions to attract and retain health workers in remote and rural areas from an impact evaluation perspective. It reports on a literature review of studies that have conducted evaluations of such interventions. It presents a synthesis of the indicators and methods used to measure the effects of rural retention interventions against several policy dimensions such as: attractiveness of rural or remote areas, deployment/recruitment, retention, and health workforce and health systems performance. It also discusses the quality of the current evidence on evaluation studies and emphasizes the need for more thorough evaluations to support policy-makers in developing, implementing and evaluating effective interventions to increase availability of health workers in underserved areas and ultimately contribute to reaching the United Nations' Millennium Development Goals.